Indonesia-South Korea Cooperation in the Realization of Net Zero Emissions through the KBLBB Program - Elika Puspa Maharani; Triesanto Romulo Simanjuntak; Novriest Umbu W. Nau (Asosiasi Dosen Muda Indonesia, 2025)
This study analyzes Indonesia's cooperation with South Korea in realizing Net Zero Emission (NZE) through the Battery-Based Electric Motor Vehicle (KBLBB) program. With the Theory of Environmentalism, the Concept of Anthropocentrism and the Concept of Environmental Regime, this study explores how the KBLBB program can be one of the strategic programs for mitigating climate change in the energy sector, especially transportation. Indonesia as one of the contributors to global greenhouse gas emissions, requires solutions to reduce carbon emissions and accelerate the green energy transition. With reference to the UNFCCC through the Long-Term Strategy for Low Carbon and Climate Resilience (LTS-LCCR), there are several targets that need to be achieved by Indonesia in the short, medium and long term for the realization of NZE 2060. However, Indonesia faces several challenges in developing infrastructure and production of electric vehicles, which requires Indonesia to partner with South Korea through the Indonesia-Korea Comprehensive Economic Partnership Agreement (IK-CEPA). This study reveals the importance of bilateral collaboration, technology transfer and investment to accelerate KBLBB.